Studi Literatur : Analisis Pengaruh Penerapan Audit Manajemen Sumber Daya Manusia Terhadap Kinerja Karyawan - Phia Lazara; Miftahul Wahidah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to determine the effect of implementing a Human Resource Management Audit on employee performance. This research was conducted using the literature study method by reviewing and analyzing 10 articles. This research also aims to measure the efficiency and effectiveness of Human Resources on Employee Performance. From the results of the study and literature analysis of the most results, it can be concluded that the implementation of human resource management audits has a positive and significant effect on employee performance.